Sterically Encumbered Iridium Bis(N-heterocyclic carbene) Complexes: Air-Stable 14-Electron Cations and Facile Degenerate C-H Activation - Phillips, N; Rowles, J; Kelly, M; Riddlestone, I; Rees, N; Dervisi, A; Fallis, I; Aldridge, S (2012)
Cationic Ir(III) systems supported by a bis(expanded NHC) framework and featuring both agostic C-H and cis alkyl/hydride ligand sets have been targeted by protonation of the corresponding bis(alkyl) hydride complexes. Remarkably, the steric shielding afforded by the NHC substituents is such that these and related putative 14-electron cations are air and moisture stable. In solution, degenerate fluxional exchange is brought about by reversible σ-bond activation within the agostic alkyl C(sp3)-H bond; a non-dissociative mechanism is implied by the activation parameters ΔH‡ = 8.8(0.4) kcal mol-1 and ΔS‡ = -12.2(1.7) eu. © 2012 American Chemical Society.